2022
DOI: 10.1039/d2cc02356c
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting consecutive photoinduced electron transfer (ConPET) in CO2 photoreduction

Abstract: The consecutive photoinduced electron transfer (ConPET) process of 1,2,3,5-Tetrakis(carbazol-9-yl)-4,6-dicyanobenzene (4CzIPN) in CO2 photoreduction to achieve powerful reducing species has been disclosed by activating a bis(terpyridine)ruthenium(II) complex bearing a high overpotential...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 38 publications
(20 reference statements)
1
14
0
1
Order By: Relevance
“…The new absorption band was ascribed to the ligand-based radical anion of terpyridine (tpy •– ) in G1 , resulting from the electron transfer process from 4CzIPN to terpyridine units. It has been reported that terpyridine-based radical anions exhibit an absorption band around 600 nm, which can further interact with CO 2 . , As shown in Figure f, this absorption band at 605 nm went down slowly in the dark under a N 2 atmosphere. However, it can disappear in 2 min under a CO 2 atmosphere, suggesting the ligand-based electron transfer between G1 and CO 2 (Figure S18).…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…The new absorption band was ascribed to the ligand-based radical anion of terpyridine (tpy •– ) in G1 , resulting from the electron transfer process from 4CzIPN to terpyridine units. It has been reported that terpyridine-based radical anions exhibit an absorption band around 600 nm, which can further interact with CO 2 . , As shown in Figure f, this absorption band at 605 nm went down slowly in the dark under a N 2 atmosphere. However, it can disappear in 2 min under a CO 2 atmosphere, suggesting the ligand-based electron transfer between G1 and CO 2 (Figure S18).…”
Section: Resultssupporting
confidence: 66%
“…Therefore, the electron transfer from 4CzIPN* to assemblies A1 , A2 , and G1 is feasible due to the fact that the CB potentials of the three assemblies are more positive (>−0.94 V) (Figure d), which is also verified by the PL quenching experiments (Figure d). However, 4CzIPN* can also be reductively quenched by the sacrificial electron donor TEA to generate the reduced state of 4CzIPN (4CzIPN •– ) . Then, the electron transfer from the species 4CzIPN •– ( E red = −1.0 vs NHE) to assemblies A1 , A2 , and G1 is also feasible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that Ir(ppy) 3 in the photoexcited sate is a modest reductant with a reduction potential about −1.70 V vs. SCE which is strong enough for promoting the reduction of Bptpy + to Bptpy 0 (−0.96 V). However, 4CzIPN is reported to generate a highly reducing species upon light irradiation that could even reduce 1,4‐dichlorobenzene with a potential about −2.24 V [48] . Therefore, 4CzIPN used here is powerful enough to reduce Bptpy + to Bptpy − as shown in Figure 4f at the step (4).…”
Section: Resultsmentioning
confidence: 85%
“…To evaluate the photocatalytic performance of Bptpy + as a molecular photocatalyst in CO 2 RR, the organic photosensitizer 4CzIPN was used as the photosensitizer because it was found to be a powerful photosensitizer in our previous studies. [16,[46][47][48] As can be seen from Figure 3, photocatalytic reactions have been performed under various conditions. Figure 3a shows the yield of CO is related to the volume of water in the reaction solution.…”
Section: Resultsmentioning
confidence: 99%